Tdap and Influenza Vaccination Among Women with a Live Birth, Internet Panel Survey, United States, 2015–2016. (4th October 2017) - Black, Carla; Ding, Helen; Kahn, Katherine; Ball, Sarah; Fink, Rebecca; Devlin, Rebecca; Fiebelkorn, Amy Parker; D'Angelo, Denise; Greby, Stacie
Abstract: Background: The Advisory Committee on Immunization Practices recommends that all pregnant women receive a tetanus diphtheria toxoids and acellular pertussis vaccine (Tdap) during each pregnancy and an influenza vaccination annually. Methods: An opt-in Internet panel survey was conducted March 29-April 7, 2016 among women who reported being pregnant any time since August 1, 2015 to assess vaccination coverage with influenza and Tdap among pregnant women and explore reasons for non-vaccination. Analysis was restricted to women who delivered a live birth between August 1 and the time of survey. Respondents were asked about receipt of influenza vaccination since July 1 and Tdap during their most recent pregnancy, if a provider recommended or offered vaccination, and vaccination-related knowledge, attitudes, and beliefs. Estimates were weighted by age, race/ethnicity, and census region to the U.S. pregnant women population. Results: Among 663 women, 28.8% reported receiving both influenza and Tdap vaccination, 14.9% received influenza vaccination only, and 20.0% received Tdap only. 70.3% of women received a provider recommendation for both vaccines, 16.8% were recommended influenza vaccine only, 6.5% were recommended Tdap only, and 6.4% received no vaccine recommendation. The corresponding estimates for receipt of a provider offer of vaccination were 52.9%, 21.1%, 10.7%, and 15.3%, respectively. The top reported reasons for non-vaccination with influenza vaccine, regardless whether or not Tdap was received, were not thinking the vaccine is effective and fear of getting sick/side effects from the vaccine. The top reported reasons for non-vaccination with Tdap, regardless whether or not influenza vaccination was received, were not knowing they were supposed to get Tdap and not getting a provider recommendation for Tdap. Conclusion: Less than 30% of pregnant women reported being fully vaccinated with recommended maternal vaccines, leaving them and their infants at risk of vaccine-preventable disease. Reported reasons for non-vaccination differed by vaccine: primarily negative attitudes toward influenza vaccine and lack of awareness of the need for Tdap. Clinic-based education along with systems such as standing orders and provider reminders are strategies to increase maternal vaccination. Disclosures: All authors: No reported disclosures.